Nitric oxide alterations in cardiovascular system of rats with Parkinsonism induced by 6-OHDA and submitted to previous exercise - de Jager, Lorena; Amorim, Eric Diego Turossi; Lucchetti, Bruno Fernando Cruz; Lopes, Fernanda Novi Cortegoso; Crestani, Carlos Cesar [UNESP]; Pinge-Filho, Phileno; Martins-Pinge, Marli Cardoso (Elsevier, 2018)
Studies showed that physical exercise decreases the risk of developing Parkinson's disease (PD) as slowing its progression. Nitric oxide (NO) increases in the substantia nigra pars compacta (SNpc) of individuals with PD. However, no study has evaluated the effects of exercise on peripheral NO levels and its modulatory effects on cardiovascular dysfunctions of subjects with PD. Trained (T) or sedentary (S) animals underwent stereotactic surgery for bilateral 6-hydroxydopamine (6-OHDA) or vehicle microinfusion (Sham group). After 6 days, the animals were catheterized for baseline parameters, followed by inhibition of NOS by Nw-nitro-arginine-methyl ester (L-NAME, 10 mg/kg - i.v.). Nitrite concentration was performed in the aorta, heart, kidney, adrenal and plasma. After exercise, the animals presented resting bradycardia (6-OHDA T and Sham T). NO was increased in the aorta of 6-OHDA S, and decreased in 6-OHDA T animals. In the heart, NO was increased in Sham T compared to sedentary and decreased in 6-OHDA T relative to 6-OHDA S and Sham T animals. At the kidney, NO decrease in 6-OHDA S and Sham T when compared to Sham S and, in adrenal gland, there was a decrease in 6-OHDA T in relation to 6-OHDA S. L-NAME promoted lower increases in MAP in 6-OHDA groups. The decreases of HR were enhanced due to physical training. 6-OHDA S group presented decreased systolic arterial pressure variability, not altered by exercise. Our data showed alterations in peripheral NO in the association of exercise with Parkinsonism in the cardiovascular function.
Keywords: Arterial pressure; Heart rate; L-NAME; Parkinson's disease; Swimming